The Syntax Of Emojis Semantic Shifts And Grammatical Evolution In Global Digital Communication - Agustina, Sitti; Rachman, Azhariah; Fitri, Silva; Silva, Maria (Yayasan Adra Karima Hubbi, 2025)
Background. The rapid proliferation of emojis as visual symbols in global digital communication has transformed the way meaning, emotion, and grammar are expressed in online discourse. Once viewed merely as decorative icons, emojis have evolved into semiotic units that participate in syntactic and pragmatic structures across languages and cultures. Purpose. This study investigates how emojis contribute to semantic shifts and grammatical innovation in digital interaction, focusing on their function as modifiers, predicates, and discourse markers in written communication. The research aims to analyze the syntactic integration of emojis within linguistic systems and to explore how users employ them to construct meaning beyond traditional textual boundaries. Method. A qualitative linguistic approach combined with corpus-based discourse analysis was utilized to examine 10,000 social media posts collected from multilingual digital platforms, including Twitter, WhatsApp, and Instagram. Results. The findings reveal that emojis operate according to emerging syntactic patterns, functioning as replacements for verbs, adjectives, and punctuation while simultaneously encoding affective and contextual information. The study also identifies cross-cultural variations in emoji sequencing that parallel grammatical rules, suggesting the emergence of a visual-syntactic grammar in digital communication. The results demonstrate that emojis are no longer extralinguistic symbols but dynamic components of evolving global language practices. Conclusion. The study concludes that understanding the syntax of emojis provides critical insights into how digital communication fosters linguistic innovation, cultural hybridity, and multimodal literacy in the 21st century.